Functional Outcomes and Morbidity in Pediatric Sepsis Survivors: A Tanzanian Experience - Lau-Braunhut, Sarah A.; Smith, Audrey M.; Steurer, Martina A.; Murray, Brittany L.; Sawe, Hendry; Matthay, Michael A.; Reynolds, Teri; Kortz, Teresa Bleakly (Frontiers in Pediatrics, 2022)
Pediatric sepsis remains a significant cause of childhood morbidity and mortality, disproportionately affecting resource-limited settings. As more patients survive, it is paramount that we improve our understanding of post-sepsis morbidity and its impact on functional outcomes. The Functional Status Scale (FSS) is a pediatric validated outcome measure quantifying functional impairment, previously demonstrating decreased function following critical illnesses, including sepsis, in resource-rich settings. However, functional outcomes utilizing the FSS in pediatric sepsis survivors have never been studied in resource-limited settings or in non-critically ill septic children. In a Tanzanian cohort of pediatric sepsis patients, we aimed to evaluate morbidity associated with an acute septic episode using the FSS modified for resource-limited settings. This was a prospective cohort study at an urban referral hospital in Tanzania, including children with sepsis aged 28 days to 14 years old over a 12-month period. The FSS was adapted to the site’s available resources. FSS scores were obtained by interviewing guardians both at the time of presentation to determine the child’s baseline and at 28-day follow-up. The primary outcome was ‘decline in functional status’, as defined by a change in FSS score of at least 3. In this cohort, 4.3% of the 1,359 surviving children completing 28-day follow-up had a ‘decline in functional status’. Conversely, 13.8% of guardians reported that their child was not yet back to their pre-illness state. Three-quarters of children reported as not fully recovered were not identified via the FSS as having a decline in functional status. In our cohort of pediatric sepsis patients, we identified a low rate of decline in functional status when using the FSS adapted for resource-limited settings. A higher proportion of children were subjectively identified as not being recovered to baseline. This suggests that the FSS has limitations in this population, despite being adapted for resource-limited settings. Next steps include developing and validating a further revised FSS to better capture patients identified as not recovered but missed by the current FSS.